(untitled) (Research, Society and Development, 2022)
Objective: To disseminate the experience of teaching Integrative and Complementary Practices in Health (PICS) in undergraduate courses with the disease. Method: This is an experience report in the PICS discipline, carried out in a synchronous virtual environment, not in a nursing course at the Federal University of Sergipe. Results: The course provided innovative content, essential for understanding what comprehensive care really means, as well as knowledge of all the PICS available to them by Sistema Único de Saúde and their possibilities for health and nursing care. In addition, it makes effective self-care strategies in order to improve the quality of life of two students. Conclusion: The experience of the PICS teaching-learning process was not a successful nursing course, or one that encourages the continuation of teaching in Higher Education Institutions. To teach PICS is to contribute to the implementation of two SUS principles, promoting comprehensive health care.